Exploring the resistance of pigmented rice to brown planthopper (Nilaparvata lugens Stål) by phenotypic and genotypic analyses - Chaerani,; Yunus, Muhamad; Hidayatun, Nurul; Tasliah,; Galurina, Rina Siti; Matsohan,; Andarini, Yusi Nurmalita; Risliawati, Andari (Universiti Kebangsaan Malaysia, 2024)
Developing new pigmented rice varieties that meet consumers’ preferences requires addressing resistance to brown planthopper (BPH), a highly destructive insect pest of rice. To effectively manage this pest, it is essential to explore BPH resistance genes from rice germplasms and incorporate them into elite varieties. The objective of this study was to identify the source of resistance among local and improved pigmented rice varieties in Indonesia against field BPH. Furthermore, the study aimed to characterize their genetic diversity using molecular markers associated with Bph genes and functional markers for these genes. Eighty-eight local varieties from the Indonesian Agricultural Gene Bank, collected across 18 provinces between 1971 and 2019, and four improved varieties, were evaluated using the standard seed box screening test method. Among these entries, 6 local accessions and 1 improved variety exhibited moderate resistance. Genetic analysis of these entries and three randomly selected susceptible entries using 12 SSR and InDel markers associated with Bph gene loci showed that the moderately resistant entries had higher allele numbers (11 to 13) compared to the susceptible entries (4 to 7). These markers could distinguish the resistant group from the susceptible ones in cluster analysis. Genotyping using functional markers further showed that the moderately resistant entries had 2 to 4 combinations of Bph genes. In contrast, the susceptible entries contained neither Bph genes nor only one gene. Local accessions with a 2 to 4 Bph gene combination can be donors of BPH resistance in improving pigmented rice varieties.